Redução, intencionalidade, mundo : a fenomenologia Husserliana como superação da oposição entre realismo e idealismo - Missaggia, Juliana Oliveira (2015)
This work deals with the issue of determining the position of Edmund Hesserl's philosophy in relation to the traditional philosophical opposition between realism and idealism. We argue that the German thinker, through the development of the phenomenological method, proposes a new kind of idealim that does not fit this antinomy as expressed by history in philosophy until the down of contemporaneity, which results in an original solution for the issue. In order to support this thesis we analyze focal concepts developed by Husserk after the so-called "idealist turn" of this ideas, among which we wmphasize the nations of phenomenological reduction, noesis, noema, lifeworld, body, and inter-subjectivity. Throughout this study we also aimed to show how Husserlian philosophy, especially during its later phases, was the precurso of many of the themes which are dear to other phenomenilogists, like Heidegger and Merleau-Ponty, who are usually seen as thinkers who radically broke with the method proposed by Husserl. Thus, we position ourselves against interpretations which see Phenomenology as a philosophy qhich represents idealism similar to those by Kant or Berkeley, and we also deny that the innovation put forward by Husserl is due to the lack of ontology in his ideas. Besides, we critically analyse the Husserlian philosophy, briefly pointing the main difficulties we find in his project.